Early Paleozoic rifting and reactivation of a passive-margin rift: Insights from detrital zircon provenance signatures of the Potsdam Group, Ottawa graben: Comment - E. Landing; Hersi, Osman Salad; L. Amati; Westrop, Stephen R.; Franzi, David A. (GSA Bulletin, 2019)
This comment outlines fundamental problems in Lowe et al.’s synthesis (2018) of the early Paleozoic stratigraphic architecture of the eastern Ottawa-Bonnechere aulacogen that preclude an accurate analysis of the region’s geological and depositional history and even an adequate stratigraphic provenance of the detrital zircons that they analyze. These problems include: inaccurate lithostratigraphic and contradictory biostratigraphic correlations that have also led to extension of the Potsdam “Group” into the Lower Ordovician; a proposed allostratigraphy that contradicts itself when tested with existing litho- and biostratigraphic data; redefinitions of earlier defined lithostratigraphic units that lead to confusion on close reading; and errors in interpreted depositional environments and lithostratigraphic contacts.